Pengalaman Church Planting di Era Pandemi Covid-19: Sebuah Interpretative Phenomenological Analysis - Kawangmani, Soleman (SOPHIA: Jurnal Teologi dan Pendidikan Kristen, 2021)
Abstract: New local Church Planting (CP) is an effective way of carrying out the Great Commission. CP must continue to be implemented in any situation and condition, including in the era of the Covid-19 pandemic. The aim of the research is to find the servants of Christ interpret their experiences in doing CP in the era of the Covid-19 pandemic. This study uses a qualitative approach with phenomenological methods. The analysis technique is Interpretative Phenomenological Analysis (IPA). Determination of the sample using purposive sampling technique. The results showed that there were five main themes, namely, first, CP as a form of obedience to the Vision of God; second, the Covid-19 pandemic era as an opportunity and opportunity for CP; third, in CP there is love and social care in a real and holistic manner; fourth, there is Covid-19 pandemic education as a form of national responsibility; fifth, the results of the CP, namely the establishment of a church coaching group and the CP had a positive impact on the commitment to serve and the increased participation of the congregation in CP services. A special theme is the need for the involvement of servants in the community of God's servants from an early age to strengthen each other in CP services. Keywords: Experience, Church planting, Covid-19 pandemic era, Interpretative phenomenological analysis Abstrak: Penanaman gereja (Church Planting-CP) lokal baru merupakan cara yang efektif dalam melaksanakan Amanat Agung. CP harus terus dilaksanakan dalam situasi dan kondisi apapun termasuk di era pandemi Covid-19. Tujuan penelitian yaitu untuk mengetahui para pelayan Kristus memaknai pengalamannya dalam melakukan CP di era pandemi Covid-19. Penelitian ini menggunakan pendekatan kualitatif dengan metode fenomenologi. Teknik analisis yaitu Interpretative Phenomenological Analysis (IPA). Penentuan sampel menggunakan teknik purposive sampling. Hasil penelitian menunjukkan adanya lima tema utama yaitu, pertama, CP sebagai wujud ketaatan terhadap Visi Allah; kedua, era pandemi Covid-19 sebagai kesempatan dan peluang CP; ketiga, dalam CP ada kasih dan kepedulian sosial secara nyata dan holistik; keempat, ada edukasi pandemi Covid-19 sebagai wujud tanggung jawab warga negara; kelima, hasil CP yaitu berdirinya kelompok pembinaan jemaat dan CP berdampak positif terhadap komitmen melayani serta meningkatnya partisipasi jemaat dalam pelayanan CP. Tema khusus yaitu pentingnya keterlibatan pelayan dalam komunitas hamba Tuhan sejak dini untuk saling menguatkan dalam pelayanan CP. Kata Kunci: Pengalaman, Penanaman gereja, Era pandemi Covid-19, Interpretative phenomenological analysis